Air pollution, coronary artery disease, and cardiovascular events: Insights from the PROMISE trial - Langenbach, Marcel Christian; Mayrhofer, Thomas; Langenbach, Isabel L.; Lu, Michael T.; Karady, Julia; Maintz, David; Abohashem, Shady; Tawakol, Ahmed; Pagidipati, Neha J.; Shah, Svati H.; Ferencik, Maros; Motsinger-Reif, Alison; et al. (Journal of cardiovascular computed tomography, 2025)
Background - Air pollution is associated with mortality and major adverse cardiovascular events (MACE) in the general population. However, little is known about the relationship between air pollution and coronary artery disease (CAD) and how this relates to MACE. - Methods - This study utilized data from the computed tomography (CT) arm of the PROMISE trial investigating symptomatic individuals with suspected CAD. We linked levels of air pollutants (PM2·5, PM10, NO2, and ozone) at U.S. zip codes of residence CT-derived CAD and adjudicated MACE (all-cause death, myocardial infarction, and hospitalization for unstable angina). Multivariable analyses were adjusted for the ASCVD risk score and socioeconomic determinants of health. Mediation analyses were used to test putative pathways. - Results - In 4343 individuals (48 ​% males; age: 61 ​± ​8 years), elevated exposures to PM2.5 (≥9.4 ​μg/m3) and NO2 (≥5.3 ​ppb) were independently associated with obstructive CAD (aOR ​= ​1.23, 95%CI: 1.03-1.48, p ​= ​0.024; aOR ​= ​1.56, 95%CI: 1.02-2.40, p ​= ​0.042), while there were no significant associations with PM10 (≥15 ​μg/m3) or ozone (≥51 ​ppb). Increased PM2.5, PM10 and ozone were independently associated with MACE (aHR ​= ​1.56, 95%CI: 1.12-2.18, p ​= ​0.008; aHR ​= ​2.09, 95%CI: 1.18-3.70, p ​= ​0.011, aHR ​= ​1.96, 95%CI: 1.20-3.21, p ​= ​0.008). In the mediation analysis, obstructive CAD accounted for 9 ​% of the total effect (p ​= ​0.012) between PM2.5 and MACE. - Conclusion - Exposure to air pollution, particularly PM2.5, was independently associated with obstructive CAD and MACE, with obstructive CAD mediating a small but significant portion of the association between air pollution and MACE.
Online verfügbar: 19. März 2025, Artikelversion: 13. Juni 2025
Gesehen am 21.08.2025